2015
DOI: 10.1016/j.tranon.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging in Meningioma: Prediction of Tumor Grade and Association with Histopathological Parameters

Abstract: OBJECTIVES: To analyze diffusion-weighted imaging (DWI) findings of meningiomas and to compare them with tumor grade, cell count, and proliferation index and to test a possibility of use of apparent diffusion coefficient (ADC) to differentiate benign from atypical/malignant tumors. METHODS: Forty-nine meningiomas were analyzed. DWI was done using a multislice single-shot echo-planar imaging sequence. A polygonal region of interest was drawn on ADC maps around the margin of the lesion. In all lesions, minimal A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
85
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 25 publications
(53 reference statements)
15
85
4
1
Order By: Relevance
“…It has been shown that ADC correlated well with proliferation index KI 67 in different lesions [5, 7, 16]. Furthermore, as reported previously, ADC also correlated inversely with cell count and nuclear areas [4, 6, 17].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…It has been shown that ADC correlated well with proliferation index KI 67 in different lesions [5, 7, 16]. Furthermore, as reported previously, ADC also correlated inversely with cell count and nuclear areas [4, 6, 17].…”
Section: Introductionsupporting
confidence: 65%
“…These relationships were documented in sarcomas, meningiomas, and several epithelial tumors [7, 16, 31]. In rectal cancer, only few studies investigated correlations between DWI and histopathological findings [23, 24, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…ADC maps and postcontrast T 1 W images were included in the present study mainly for two reasons: 1) because most of the previous studies trying to determine meningioma grading from MR images were focused on these two imaging sequences; 2) because the combination between semantic and radiomic features on postcontrast T 1 W images has recently shown promising results with an AUC of 0.86 . The possibility to determine the grading of human meningiomas using diffusion‐tensor imaging has been explored by several authors, with differing results. In particular, a study by Surov et al including 389 meningioma‐affected patients reported an ADC value below 0.85 × 10 ‐3 mm 2 s ‐1 having a 73% accuracy (72.9% sensitivity and 73.1% specificity) in the distinction between benign and atypical/malignant meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility to determine the grading of human meningiomas using diffusion‐tensor imaging has been explored by several authors, with differing results. In particular, a study by Surov et al including 389 meningioma‐affected patients reported an ADC value below 0.85 × 10 ‐3 mm 2 s ‐1 having a 73% accuracy (72.9% sensitivity and 73.1% specificity) in the distinction between benign and atypical/malignant meningiomas. By contrast, Santelli et al and Sanverdi et al found no statistically significant differences between the ADC calculated on benign and on atypical/malignant lesions in 177 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple deposits were also observed in other extracranial sites in previous reports of soft tissue metastasis from malignant meningioma [3, 4]. The tumour in the frontal lobe showed several radiological findings that have been described as potential markers of atypical or malignant meningiomas including indistinct or irregular tumour margins, marked peritumoral oedema, inhomogeneous enhancement post-contrast, intrinsic cyst-like areas, disruption of the arachnoid at the brain-tumour interface and adjacent bone destruction [18–24]. …”
Section: Discussionmentioning
confidence: 59%